Experimental study on flow boiling characteristics in a high aspect ratio vertical rectangular mini-channel under low heat and mass flux - Liu, Jiayao; Liu, Jinping; Li, Rixin; Xu, Xiongwen (Experimental thermal and fluid science, 2018)
•New flow boiling data of R600a, R227ea and R245fa in a rectangular mini-channel.•Five flow patterns and activated nucleate boiling sites in liquid film are observed.•Effects of heat flux, mass flux, quality and saturation pressure are investigated.•Flow boiling heat transfer mechanism is analysed.•Predictive correlations are comparatively evaluated based on the experimental data. This study investigates the flow patterns and flow boiling characteristics of R600a, R227ea and R245fa in a visualized vertical rectangular mini-channel, with a moderate-high aspect ratio (width/height = 6.25, cross-section area of 1.6 mm × 10 mm and length of 520 mm. The experimental results are obtained at saturation temperatures of 27.5, 36.6 and 45.5 °C, with relatively low heat and mass flux ranging from 3.60 to 10.50 kW/m2 and 32.20 to 116.8 kg/m2 s, respectively. Five flow types are identified and a flow pattern map is plotted. Front waves are observed and minimized bubbles are detected, generated from the slug to the churn-annular liquid film. The effects of heat flux, mass flux, vapor quality and saturation pressure on flow boiling are investigated and analysed. For all three tested refrigerants, the heat flux and saturation pressure are found to have a significant influence on the heat transfer coefficient, while the effects of the mass flux and vapor quality are negligible. Eleven existing correlations are comparatively evaluated based on the experimental data. The dimension groups correlation exhibits superior predicting performance, and a new correlation is developed for low heat and fluxes flow boiling in vertical minichannel.